2020
DOI: 10.48550/arxiv.2009.00657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$T\overline{T}$-deformation of $q$-Yang-Mills theory

Leonardo Santilli,
Richard J. Szabo,
Miguel Tierz

Abstract: We derive the T T -perturbed version of two-dimensional q-deformed Yang-Mills theory on an arbitrary Riemann surface by coupling the unperturbed theory in the first order formalism to Jackiw-Teitelboim gravity. We show that the T T -deformation results in a breakdown of the connection with a Chern-Simons theory on a Seifert manifold, and of the large N factorization into chiral and anti-chiral sectors. For the U (N ) gauge theory on the sphere, we show that the large N phase transition persists, and that it is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…These deformed theories can be well controlled by the fact that many quantities in the deformed theory, such as S-matrix, energy spectrum, wilson loop, correlation functions, entanglement entropy and so on can be computed analytically [2,8,33,34,35,36,37,38,39], in particular when the un-deformed theory is a CFT. These deformations also attracts much further attention from both field theory [40,41,42,43,44,45,46,47,48,49,50,51] and holographic perspectives [52,53,54,55,56,57,58,59,60,61,62,63].…”
mentioning
confidence: 99%
“…These deformed theories can be well controlled by the fact that many quantities in the deformed theory, such as S-matrix, energy spectrum, wilson loop, correlation functions, entanglement entropy and so on can be computed analytically [2,8,33,34,35,36,37,38,39], in particular when the un-deformed theory is a CFT. These deformations also attracts much further attention from both field theory [40,41,42,43,44,45,46,47,48,49,50,51] and holographic perspectives [52,53,54,55,56,57,58,59,60,61,62,63].…”
mentioning
confidence: 99%
“…It is based on the factorization of the gauge theory into chiral and anti-chiral sectors in the large N limit, which follows immediately from the fermionic picture. The T T -YM/string theory correspondence has been recently discussed [32,33]. It has been shown that the T T -YM theory is mapped onto a system of fermions experiencing highly non-local interaction that prevents their factorization.…”
Section: Discussionmentioning
confidence: 99%
“…The T T deformation of the YM theory has been studied in various contexts [29][30][31][32] by now. Also, new phenomena have been discovered [33,34]. The clear particle-like interpretation, though, seems to have been lost after the deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we present a few comments on the recent paper [31]. We analyze the peculiarities of the DK phase transition in T T -deformed q-YM on a sphere for p ≤ 2.…”
Section: Comment On T T -Deformed Q-ymmentioning
confidence: 99%
“…The deformation preserves the order of the transition and its instanton interpretation but the critical area gets renormalized non-trivially A → Ab ∞ (τ, A). The DK phase transition for the T 2 deformed 2d q-YM theory has been discussed as well [31]. It was emphasized that the free fermion picture for the T 2 deformed theory is lost.…”
Section: Introductionmentioning
confidence: 99%